Enhancing sulfasalazine solubility in supercritical carbon dioxide with ethanol cosolvent: a comprehensive study - Hadil Faris Alotaibi; Suleiman Ibrahim Mohammad; Asokan Vasudevan; Suranjana V. Mayani; Suhas Ballal; Munthar Kadhim Abosaoda; Abhayveer Singh; Subhashree Ray; Atreyi Pramanik (Scientific Reports)
Abstract In this study, the solubility of sulfasalazine in supercritical carbon dioxide, using ethanol as a cosolvent, was evaluated at temperatures of 308, 318, 328, and 338 K, and at pressures reaching up to 30 MPa. A comprehensive examination was conducted to ascertain the impact of temperature, pressure, and cosolvent concentration on solubility and density. To this end, SRK as an equation of state and a range of semi-empirical correlations were employed to correlate the solubility. The Soltani-Mazloumi and Madras et al. models were identified as the most suitable model for the experimental data. The mole fraction of sulfasalazine ranged from 0.273 × 10−4 to 1.654 × 10−4 in the binary system, and from 1.535 × 10−4 to 5.211 × 10−4 and 3.263 × 10−4 to 11.451 × 10−4 at concentrations of 1 and 3 mol%, respectively. The findings indicated that the incorporation of a cosolvent, notably ethanol, led to a substantial enhancement in solubility. The sulfasalazine-ethanol-CO2 system demonstrated the highest solubility at 12 MPa and 338 K, exhibiting approximately 11.95 times greater solubility compared to that observed in pure supercritical CO2.